2022
DOI: 10.1111/ele.13989
|View full text |Cite
|
Sign up to set email alerts
|

Smaller adult fish size in warmer water is not explained by elevated metabolism

Abstract: Fish and other ectotherms living in warmer waters often grow faster as juveniles, mature earlier, but become smaller adults. Known as the temperature-size rule (TSR), this pattern is commonly attributed to higher metabolism in warmer waters, leaving fewer resources for growth. An alternative explanation focuses on growth and reproduction trade-offs across temperatures. We tested these hypotheses by measuring growth, maturation, metabolism and reproductive allocation from zebrafish populations kept at 26 and 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
59
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 74 publications
9
59
1
Order By: Relevance
“…This result was unexpected for two reasons: optimum growth temperatures generally decline with body size within species under food satiation in experimental studies (Lindmark et al . 2022), and fish tend to mature at smaller body size and allocate more energy into reproduction as it gets warmer (Wootton et al . 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was unexpected for two reasons: optimum growth temperatures generally decline with body size within species under food satiation in experimental studies (Lindmark et al . 2022), and fish tend to mature at smaller body size and allocate more energy into reproduction as it gets warmer (Wootton et al . 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Size-at-age is generally predicted to increase with warming for small individuals, but decrease for large individuals according to the mentioned TSR (Atkinson 1994; Ohlberger 2013). Several factors likely contribute to this pattern, such as increased allocation to reproduction (Wootton et al . 2022) and larger individuals in fish populations having optimum growth rates at lower temperatures (Lindmark et al .…”
Section: Introductionmentioning
confidence: 99%
“…A number of experimental and modelling studies have reported that warming waters will lead to smaller fish (Daufresne et al 2009, Cheung et al 2013, Pauly and Cheung 2018). At an intraspecific level this is believed to be driven by the thermal dependence of physiological processes (Angilletta Jr et al 2004, Brown et al 2004, Forster et al 2011), although the exact mechanisms remain debated (Pauly and Cheung 2018, Audzijonyte et al 2019a, Wootton et al 2022). In contrast our study reports that physiological responses to warming generally increased, rather than decreased, mean species body sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Some degree of growth-reproduction trade-off does occur in size-based models, because growth and therefore maturation (set to occur over some size range) are not set, but are emergent model properties (Andersen et al 2007). Recent inter-generational experiments show that some populations may be capable of complete metabolic acclimation to higher temperatures, and that changes in growth and size may be largely driven by reproductive decisions (Wootton et al 2022). Future studies should explore more direct impacts of temperature on these trade-offs by allowing decreasing maturation sizes, consistent with TSR observations and different reproductive allocation curves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation